(untitled) (Research, Society and Development, 2021)
Objective: To analyze the nurses’ knowledge regarding the immediate and immediate care provided to the newborn in the Normal Birth Centers (CNP) in the city of Manaus-AM. Methodology: This is a qualitative, descriptive, exploratory study, carried out with 11 nurses who worked at the Intra-hospital Normal Childbirth Center, located in the East Zone of the city of Manaus-Am, from July to September 2017. It used as a data collection instrument, a semi-structured interview script divided into two stages. In the first stage, the information related to the variables sex, age, time since graduation and performance. In the 2nd stage, open questions were made, aimed at the nurses’ knowledge about the immediate and immediate care offered to the newborn. Descriptive statistical analysis was carried out through RStudio with the data from the first stage and thematic analysis referring to the open questions in the second stage. Results: The speeches revealed the nurses’ perception about the care of the NB during childbirth and birth, care routines and practices, and the importance of training aimed at immediate and immediate care actions for the newborn to be carried out more frequently by nurses at the ANC so that risk situations are minimized in this phase. Final Considerations: This study made it possible to analyze the knowledge of obstetric nurses related to nursing care for newborns at the Center for Normal Childbirth, causing a reflection on the view of this professional regarding assistance in childbirth and birth.